Inteligencia emocional y la formación profesional de los estudiantes de la carrera de Psicopedagogía de la Universidad Nacional de Chimborazo. - Ortiz Guillen, Adriana Patricia (2024)
The present research work, has as an objective to determine the relationship between emotional intelligence and professional formation of students of the Psychopedagogy career of Universidad Nacional de Chimborazo, the development of emotional intelligence within professional formation allows students to self-regulate their emotions and become able to understand the emotions of the people around them, the research was supported by information from primary sources and the contribution of the researcher with the criteria based on reality. The methodology had a quantitative approach, because the objectivity of the results of both variables intervened. For the first variable, it was applied a psychometric technique, with the instrument being the Test TMMS-24 which measured the three subscales of emotional intelligence in the sample of the seventh semester students; while for the second variable it was used a survey technique with the instrument being a questionnaire, which was directed to the same sample of 36 students, in order to obtain numerical data. According to the SPS program, though a Pearson correlation it was obtained that the relationship between emotional intelligence and professional formation in women presents a value of 0.164 interpreted as a weak relationship; while in men the relationship is exposed with a value of .000 so it is ruled out that there is a relationship between both variables.